THE PEDAGOGICAL SIGNIFICANCE OF STUDYING THE CATEGORY OF CHILDREN WITH DELAYED MENTAL DEVELOPMENT - Kabirova Zarnigor Raxmonjon qizi (Galaxy International Interdisciplinary Research Journal, 2023)
This article aims to fully reveal the categories of children with weak mental development. Explanations are also given about the pedagogical work carried out with children of this category.